(untitled) (Research, Society and Development, 2019)
This paper aims to present some challenges arising from the construction and consolidation of professional masters in the area of Teaching in Brazil. There is also a false perception on the part of the institutions that the professional master’s degree can discredit them and that only the academic programs give prestige and promote the qualification of the university, which is a misunderstanding. To the detriment of this mistaken perception, documents such as the Capes Education Area Programs, which are organized in different proposals, constitute specific lines of research and prioritize the production of educational knowledge. Through qualitative research of an exploratory nature, we conclude that the diversity in the identity of professional masters is not only determined by its thematic area, but, fundamentally, by the great challenge of rigorously integrating research in its development process and to achieve the applicability of the results for transformation of the studied reality. From the above, we consider that historical-dialectical materialism can contribute to the epistemological understanding in the investigations of practices in educational spaces, since its ontological, axiological and gnosiological dimensions integrate a philosophy of transformation, which aims, through historical analysis and dialectic of reality, to achieve syntheses that take up, in another dimension, the initial knowledge, and aim, in the last resort, at social and collective transformation.